Recent Advances in Inorganic Solid Electrolytes for Lithium Batteries - Cao, Can; Li, Zhuo-Bin; Wang, Xiao-Liang; Zhao, Xin-Bing; Han, Wei-Qiang (Frontiers in Energy Research, 2014)
The review presents an overview of the recent advances in inorganic solid lithium ion conductors, which are of great interest as solid electrolytes in all-solid-state lithium batteries. It is focused on two major categories: crystalline electrolytes and glass-based electrolytes. Important systems such as thio-LISICON Li10SnP2S12, garnet Li7La3Zr2O12, perovskite Li3xLa(2/3)-xTiO3, NASICON Li1.3Al0.3Ti1.7(PO4)3 and glass-ceramic xLi2S•(1-x)P2S5 and their progress are described in great detail. Meanwhile, the review discusses different on-going strategies on enhancing conductivity, optimizing electrolyte/electrode interface and improving cell performance.